TEKNIK PENILAIAN FORMATIF ASPEK KOGNITIF MATA PELAJARAN PAI KURIKULUM MERDEKA - Azfar, Fani; Nisaul Ulum, Zulva Nisaul Ulum; Rachman, Abdur (Program Studi Pendidikan Agama Islam Fakultas Ilmu Tarbiyah dan Keguruan UNSIQ Jawa Tengah, 2024)
This research was conducted to improve students' understanding and skills in Islamic Religious Education subjects. Formative assessment practices are useful for successfully teaching PAI material in the independent curriculum. In presenting the data, this research uses a qualitative descriptive approach, a type of library research through various sources related to the research topic. This research aims to measure and determine the level of student's understanding through formative assessment efforts on cognitive aspects of learning outcomes. The results obtained in this research indicate that implementing cognitive assessments in Islamic Religious Education learning can be carried out using portfolio assessment models, oral, written Penilaiants, and project assessments.